The Central American Dry Corridor: A Consensus Statement and its Background - Gotlieb, Yosef (2019)
A unique gathering of climate, development and environmental experts took place from September 25-28, 2017 in San José and Guanacaste Province, Costa Rica. The subject of their deliberations was the Central American Dry Corridor (CADC),[1] which extends along the Pacific littoral from western Guatemala through northern Costa Rica.[2] This trans-frontier territory includes a population approaching 11 million, roughly a quarter of Central America’s total population. The CADC is a mainly rural area characterized by a marked precipitation seasonality, climate change vulnerability, rich biodiversity, entrenched poverty, food insecurity and outmigration.